The EPPO/OLAF compendium of national procedures: Italy - Hauck, Pierre; Schneider, Jan-Martin; Karakocaoğlu, Nur Sena; Laird, Alastair Alexander; Justus Liebig University Giessen (My University, 2026)
This Italian EPPO/OLAF volume contains a collection of Italian legislation on criminal and administrative investigations into EU fraud offences. The first part deals with the possible measures that the EPPO can take in Italy, practical examples and types of EU fraud. The second part of this volume is a compendium for OLAF investigations in Italy, referring to the Italian legislation relevant to Articles 3 to 17 of the OLAF Regulation.
Keywords: ddc:340; ddc:320